Unilateral Optic Neuropathy and Acute Angle-Closure Glaucoma following Snake Envenomation - Osman Okan Olcaysu; Kenan Cadirci; Ahmet Altun; Afak Durur Karakaya; Huseyin Bayramlar (Case Reports in Ophthalmological Medicine)
Purpose. We aimed to describe a unique case in which a patient developed unilateral optic neuritis and angle-closure glaucoma as a result of snake envenomation. Case Report. Approximately 18 hours after envenomation, a 67-year-old female patient described visual impairment and severe pain in her left eye (LE). The patient’s best corrected visual acuity was 10/10 in the RE and hand motion in the LE. Cranial magnetic resonance imaging showed signs of neuropathy in the left optic nerve. In the LE, corneal haziness, closure of the iridocorneal angle, and mild mydriasis were observed and pupillary light reflex was absent. Intraocular pressure was 25 mmHg and 57 mmHg in the RE and LE, respectively. The patient was diagnosed with acute angle-closure glaucoma in the LE. Optic neuropathy was treated with intravenous pulse methylprednisolone. Left intraocular pressure was within normal range starting on the fourth day. One month after the incident, there was no sign of optic neuropathy; relative afferent pupillary defect and optic nerve swelling disappeared. Conclusions. Patients with severe headache and visual loss after snake envenomation must be carefully examined for possible optic neuropathy and angle-closure glaucoma. Early diagnosis and treatment of these cases are necessary to prevent permanent damage to optic nerves.